Tricky Twenty-Two - Evanovich, Janet; King, Lorelei; Musselman, Dan.; Random House Audio Publishing (New York, New York : Random House Audio, 2015)
"Stephanie Plum might not be the world's greatest bounty hunter, but she knows when she's being played. Ken Globovic (aka Gobbles), hailed as the Supreme Exalted Zookeeper of the animal house known as Zeta fraternity, has been arrested for beating up the dean of students at Kiltman College. Gobbles has missed his court date and gone into hiding. People have seen him on campus, but no one will talk. Things just aren't adding up, and Stephanie can't shake the feeling that something funny is going on at the college--and it's not just Zeta fraternity pranks."
Keywords: Plum, Stephanie (Fictitious character) -- Fiction; Women bounty hunters -- Fiction -- New Jersey; College students -- Fiction; Greek letter societies -- Fiction; Murder -- Fiction -- Investigation; Audiobooks; Trenton (N.J.) -- Fiction; Mystery fiction; Audiobooks